Mimetic Governmentality and the Administration of Colonial Justice in East Timor, ca. 1860-1910 - Roque, Ricardo (2015)
This article explores the mimesis of indigenous “customs and law” as a theory of and strategy for colonial government in the period of late imperialism. I draw on the case of colonial administration in the Portuguese colony of Timor during the second-half of the nineteenth century. I introduce the concept of “mimetic governmentality”: the art of governing the Other through the productive inclusion of institutions, symbols, cultural materials, or social forms understood as other than one's own. In Timor, the imperial establishment was characterized by fragility and isolation, and a pragmatic style of colonial action thrived. In Europe, modern doctrines of colonial law rejected assimilationist policies and advocated “specialization.” In this context, between 1860 and 1910, administrators on Timor devised a system of colonial justice that required the colonizers to slip into the indigenous world and govern others from the others' position and perspectives. To efficiently govern the “natives” and apply colonial justice in courts—the so-called justiças—Europeans had to release themselves from European principles and embrace indigenous law, as they understood it. The essay uses the case of Timor to assert the analytic importance and potential of mimesis for the comparative study of colonial administrations during the period of imperial expansion.